Prof Rubens Cysne uses OECD data to discuss Social Secutiry Expenditures in Brazil - vídeo - Cysne, Rubens Penha (2017)
Related Literature can be found at http://bit.ly/2iBqKcJ and http://bit.ly/2wVjuvL.